2007
DOI: 10.2323/jgam.53.201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of herb lignin on the growth of enterobacteria

Abstract: Lignin, a natural polymer composed of phenylpropane units, is an agglutination element in the cell wall of vascular plants. These units are referred to as guaiacyl (a), syringyl (b), and p-hydroxyphenyl, (c) phenyl-propane units (Fig. 1). They are connected in three-dimensional space by C-C and C-O-C bonds. Softwood lignin consists of (a), hardwood lignin of (a) and (b), and herb lignin of (a), (b) and (c). Lignin is taken up as a "dietary fiber" when vegetables and fruits are consumed. It is thought that diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…As a sorbent, lignin may be obtained chiefly as a waste product of the paper industry, and subjected to chemical modification to increase the number of functional groups [ 21 , 22 ]. It has also been reported that lignin has multifunctional barrier properties, protecting against harmful UV radiation, as well as antibacterial properties [ 23 ]. There are also promising possibilities for the use of lignin in the pharmaceutical industry and in medicine.…”
Section: Introductionmentioning
confidence: 99%
“…As a sorbent, lignin may be obtained chiefly as a waste product of the paper industry, and subjected to chemical modification to increase the number of functional groups [ 21 , 22 ]. It has also been reported that lignin has multifunctional barrier properties, protecting against harmful UV radiation, as well as antibacterial properties [ 23 ]. There are also promising possibilities for the use of lignin in the pharmaceutical industry and in medicine.…”
Section: Introductionmentioning
confidence: 99%